2016
DOI: 10.1002/ange.201603328
|View full text |Cite
|
Sign up to set email alerts
|

Detection of LacZ‐Positive Cells in Living Tissue with Single‐Cell Resolution

Abstract: The LacZ gene,w hiche ncodes Escherichia coli bgalactosidase,iswidely used as amarker for cells with targeted gene expression or disruption. However,ithas been difficult to detect lacZ-positive cells in living organisms or tissues at single-cell resolution, limiting the utility of existing lacZ reporters.H erein we present an ewly developed fluorogenic b-galactosidase substrate suitable for labeling live cells in culture,aswell as in living tissues.This precisely functionalized fluorescent probe exhibited dram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 22 publications
0
35
0
Order By: Relevance
“…We then examined the expression of C2cd4c in the pancreas by visualizing LacZ activity. For this, we used Salmon‐gal (S‐gal; 6‐chloro‐3‐indolyl‐beta‐ d ‐galactopyranoside) in combination with Nitro Blue tetrazolium , or SPiDER‐βGal, which is rendered fluorescent by the enzymatic reaction . We visualized C2cd4c / LacZ activity during embryonic development (at E14.5–18.5) and in adult C2cd4c / LacZ KI heterozygous mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We then examined the expression of C2cd4c in the pancreas by visualizing LacZ activity. For this, we used Salmon‐gal (S‐gal; 6‐chloro‐3‐indolyl‐beta‐ d ‐galactopyranoside) in combination with Nitro Blue tetrazolium , or SPiDER‐βGal, which is rendered fluorescent by the enzymatic reaction . We visualized C2cd4c / LacZ activity during embryonic development (at E14.5–18.5) and in adult C2cd4c / LacZ KI heterozygous mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To sort senescent cells by flow cytometry, the cells were isolated from mouse corneal stroma with collagenase treatment and labeled with the cellular senescence detection kit SPiDERb-gal (Dojindo Lab, Kumamoto, Japan), as described previously. 42,43 Briefly, SPiDER-b-gal was added and incubated with the cells for 30 minutes at 378C under protection from light. After incubation, the cells were colabeled with the fibroblast marker vimentin-Alexa Fluor 647 (Abcam), washed, and sorted immediately using a FACScan flow cytometer (BD FACSAria3; BD Biosciences, San Jose, CA, USA) for SPiDER-b-galþ and vimentinþ cells.…”
Section: Flow Cytometry Assaymentioning
confidence: 99%
“…Moreover, fluorescence signal increased gradually even after removal of SPiDER-βGal. Doura et al reported that fluorescence derived from SPiDER-βGal increased with time until 120 min, the end of observation, in vitro [ 14 ], suggesting that it happens slowly in a few hours to form the protein anchored molecule from SPiDER-βGal. Thus, we speculated that SPiDER-βGal which remained inside of cell was activated by β-galactosidase and bound to intracellular protein gradually, leading to a progressive increase in fluorescence intensity even after removal of SPiDER-βGal.…”
Section: Discussionmentioning
confidence: 99%
“…SPiDER-βGal was obtained from Dojindo Molecular Technologies, Inc. (Rockville, MD, USA) [ 14 ]. gGlu-HMRG, a GGT activated fluorescence probe was synthesized as described previously [ 3 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation